Group‐Based Redistribution in Malaysia: Polarization, Incoherence, Stasis - Lee, Hwok-Aun (2024)
Group‐based redistribution is extensive and embedded in Malaysia, and has comprehensively transformed the country since the introduction of the New Economic Policy (NEP) in 1971. The NEP established a “two‐pronged” framework of poverty reduction irrespective of race and social restructuring to redress racial inequalities primarily through preferential programmes targeting the disadvantaged Bumiputera majority. The debate surrounding the NEP has under‐appreciated its strengths and augmented its omissions and misconceptions, which in turn have shaped policy discourses and attitudes in two ways. First, there is marked polarization, largely along ethnic lines, with the majority group overwhelmingly predisposed in favour of Bumiputera policy and minority groups generally wary of its continuation. The polarization unduly reduces the debate to monolithic pro‐NEP vs anti‐NEP dispositions, and constricts the solutions to a false binary question of continuing vs terminating the NEP. Second, a broad but incoherent consensus has consolidated around the notion that “need‐based” policies should comprehensively replace “race‐based” policies. While “need‐based” policies are widely embraced, they emphatically do not constitute a substitute for “race‐based” policies, or group‐based redistribution more generally. Surveys have captured the ethnic polarization surrounding “Malay privileges,” but also show that Malaysians unanimously support universal basic assistance. A systematic policy reformulation with universal basic needs and group‐based interventions as enduring and distinct domains might hold out possibilities for new and constructive compromise.